ROLE OF COMPUTED TOMOGRAPHY IN ASSESSMENT OF BLUNT TRAUMA ABDOMEN - ., Nadeem Ibrahim; ., Abdul Qayyum; ., Omar Iqbal (Pakistan Armed Forces Medical Journal, 2011)
Objectives: The objective of the study was to evaluate the usefulness of computed tomography (CT) in assessment of blunt trauma abdomen by correlating their findings with operative findings.Study Design: Validation study.Place and duration of study: Radiology Department Combined Military Hospital Rawalpindi from Aug 2005 to Aug 2006.Patients and Methods: This study involved 30 operatively managed patients. CT was carried out in all 30 patients. Sensitivity, specificity, positive predictive, negative predictive value and accuracy of CT for detection of blunt trauma abdomen were carried out by keeping operation findings as gold standard.Results: CT had shown high sensitivity (88%) in defining solid visceral injuries. Bone injuries of the pelvis identified accurately on sections reviewed with bone window settings and also the sensitivity of CT was reasonably high for bowel and mesenteric injuries (75%)Conclusion: We concluded that CT had a high sensitivity in detection of blunt trauma abdominal injuries.